Pendidikan Imu Syariah dan Hukum: Antara Tradisi Normativisme dan Empirisme serta Kemungkinan Pengembangannya - JM Muslimin (JURNAL INDO-ISLAMIKA, 2016)
This paper contradicts an idea that (Islamic law) syariah is an antithesis to human rights’ principles. Here, this paper debunks this perception as it is comparable to the way people misunderstand about syariah to criminal law. Therefore, this article demonstrates evidences that support the opposite idea; that is to say that Islamic law is in tandem with the principles of human rights and humanistic values.